Рентгенофлуоресцентный анализ следов йода в моче - Михайлов, Игорь Федорович; Будрейко, Елена Анатольевна; Батурин, Алексей Анатольевич; Шляхова, Наталия Васильевна; Михайлов, Антон Игоревич; Борисова, Светлана Серафимовна; Решетняк, Максим Вячеславович; Галата, Дарья Игоревна (Інститут медичної радіології ім. С. П. Григор'єва НАМН України, 2015)
Разработка нового метода рентгенофлуоресцентного анализа (РФА) для определения содержания следов йода в моче в диапазоне концентраций 50–200 мкг/дм³ (0,05 ÷ 0,2 ppm). Методом РФА проведено определение концентрации йода в моче у 35 детей 10–15 лет с эндокринной патологией (задержка полового развития, диффузный зоб, ожирение) и 10 практически здоровых, находившихся под наблюдением в условиях консультативной поликлиники и отделения эндокринологии ГУ "ИОЗДП НАМН Украины". Предложенный оптимизированный метод РФА позволяет на 1–2 порядка повысить чувствительность определения микроэлементов в биологических объектах и добиться определения содержания следов йода в моче в диапазоне концентраций 50–200 мкг/дм³.

Development of a new method of X-ray fluorescent analysis (XFA) for determination of iodine trace contents in urine in concentration range from 50 to200 μg/dm³ (0.05 ÷ 0.2 ppm). Materials and methods. Using XFA method, determination of iodine concentration in urine for 35 children of 10–15 with endocrine pathology (delay of sexual development, diffuse goiter, obesity) and 10 practically healthy children being observed under conditions of the consultative polyclinic and the department of endocrinology of SI "ISHCJ NAMSU". The proposed optimized XFA method allows by 1–2 orders increasing detection sensitivity for micro-elements measurements in biology objects and attaining the iodine trace contents in urine in the range from 50 to 200 μg/dm³.
X-ray fluorescent analysis of iodin traces in urine
Keywords: рентгенофлуоресцентный анализ; вторичная мишень; йодурия; микроэлементы; X-ray fluorescent analysis; secondary target; urinary iodine; micro-elements